ANALISIS KEBIJAKAN PEMULIHAN CITRA INDONESIA PADA MASA KEPEMIMPINAN PRESIDEN SBY - Muhammad Nizar Hidayat (Magister Administrasi Publik FISIP Universitas Mulawarman, 2018)
This article aim to describe and analyze President Susilo Bambang Yudhoyono’ policy in clearing up Indonesia’ national image as a country prone to terrorism. Such negative image is considered as a stumbling block to national development agenda especially in tourism. Therefore, Indonesia under the presidency of Susilo Bambang Yudhoyono were actively tried to turn the negative image in international society by doing series of diplomacies both in billateral form with United States, Australia, and Rusia, and multilateral as well as in international forums, regional and international organization such as ASEAN and the United Nations.Keyword : Regional Policy, ASEAN, Security